Maturity indices for the optimum harvest dates of "Daiane" apple designated to storage Estádio de maturação para o período ideal de colheita de maçãs 'Daiane' destinadas à armazenagem - Stanger M.C.* (2013)
The study was carried out to identify the maturity indices for the optimum harvest dates of 'Daiane' apples designated to long-term storage. Apples were harvested weekly from 113 to149 days after full bloom (DAFB), and stored for 180 or 240 days at 0.7°C under controlled atmosphere. Maturity and quality were assessed one day after harvest and after storage. Fruit quality, based on skin red color was highest when harvested lately, 149 DAFB. However, measures of firmness and taste after long-term CA storage indicated that the ideal harvest period for 'Daiane' apples should not exceed 136 DAFB. 'Daiane' apples should be picked at 121 DAFB to achieve more than half of the fruit with over 75% skin surface with red color. Therefore, the optimum harvest period for 'Daiane' apples designated to long-term storage is between 121 and 136 DAFB at orchard 1, and between 129 and 136 DAFB at orchard 2. At optimum harvest period (121-136 DAFB) 'Daiane' apple had, one day after harvest, firmness of 67-74 N, SS from 11.5 to 13%, TA of 0.26%-0.34%, starch index from 4.6 to 7.9 and background color index between 2.6 and4.0.